Аналіз нотацій моделювання бізнес-процесів щодо створення інтерактивних регламентів - Щербина, Катерина Олександрівна (НТУ "ХПІ", 2017)
Розглянуто нотації моделювання бізнес-процесів та проведено їх аналіз щодо створення інтерактивних регламентів. У статті визначено критерії для порівняльного аналізу нотацій моделювання бізнес-процесів, зважаючи на мету роботи. В результаті дослідження виявлено необхідність у створенні нової або доробці існуючої нотації, що повністю задовольняла б вимоги щодо нотації інформаційної технології, що розробляється.

Recently, in the description and modeling of regulations intensively developed and applied graphic approaches. It is recognized that graphic methods have the greatest efficiency in solving tasks related to the description, analysis and optimization of the company. In this regard, all start-up entrepreneurs are faced with the construction of business processes of their future business. Before them there is a wide selection of notations that have their advantages. This article is a continuation of the experiments described in previous publications. After conducting a comparative analysis of information technology for the creation of interactive regulations, there was a need for more detailed consideration and analysis of the notations that they use. Notices of modeling of business processes were considered and their analysis on creation of interactive regulations was conducted. In order to determine the notation that will become the tool for the information technology being developed, a number of criteria have been selected that it should satisfy. The advantages and disadvantages of the notations examined were determined and their comparison according to the selected criteria was made. As a result of the study, it was found that none of them fully meet the requirements we have set, namely: to be able to describe the regulations, to be intuitive to specialists with little or no experience in using visualization, and to have a minimum need for employee training. Thus, there is a need to create a new or complementary existing notation that fully meets these requirements. Also in the article the basis for creating the notation that will be used in the information technology being developed is chosen.
Analysis of the notations of business process modeling for the creation of interactive regulations
Keywords: інформаційна технологія; об’єктна-орієнтованість мови; навчання працівників; графічні елементи; notation; regulations; information technology